Strengthening Digital Marketing Capacity to Improve the Competitiveness of MSMEs - Teofilus Teofilus; Fahrul Riza; Endi Sarwoko (GUYUB: Journal of Community Engagement, 2026)
The uneven adoption of digital marketing among Micro, Small, and Medium Enterprises (MSMEs) in Tandes District, Surabaya, has become a significant challenge that limits business competitiveness in an increasingly digitalized economic environment. Although various government initiatives have promoted MSME digitalization, at the local level many business actors still experience limited digital literacy, inconsistent online promotional practices, and low utilization of digital platforms for market expansion. This condition highlights the urgency of implementing community service programs that focus on strengthening the digital marketing capacity of MSME actors. This community service activity aims to identify the level of knowledge and readiness of MSMEs in adopting digital marketing and to strengthen their digital marketing capacity through a participatory approach. The method used is Participatory Action Research (PAR) involving 63 MSME actors as active participants. The activities were carried out through several stages, including participatory problem identification, digital marketing training and mentoring, completion of a self-assessment instrument covering eight digital marketing competency indicators, and joint reflection and evaluation. The data were analyzed using descriptive statistics to assess readiness levels and correlation analysis to examine the relationship between digital literacy, frequency of online promotion, number of online customers, and business turnover. The results indicate that the level of digital marketing adoption among MSMEs is at a moderate level, with mean scores ranging from 2.81 to 3.22. The highest competency is the ability to identify target markets (M = 3.22), while the lowest competency relates to conducting online competitor analysis and price benchmarking (M = 2.81). Correlation analysis also shows a positive relationship between digital literacy, the intensity of online promotion, the number of online customers, and increased business turnover.